PENGARUH ENVIRONMENTAL DISCLOSURE, INSIDER OWNERSHIP DAN UKURAN PERUSAHAAN TERHADAP FIRM PERFORMANCE - Cahyani, Yenni; Ruhiyat, Endang; Holiawati, Holiawati (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
This study aims to examine and analyze the effect of Environmental Disclosure, Insider Ownership and Firm Size with Leverage as a Control Variable on Firm Performance. This research is a type of quantitative research using secondary data in the form of an annual report of 50 population of Industrial sector companies listed on the Indonesia Stock Exchange during 2017-2022 with a total of 120 observational data. The data analysis method in this study was carried out using Panel Data Regression Analysis using the statistical tool e-views 9 and obtained results that partially Envirometal Disclosure and Leverage have an effect on Firm Performance while Insider Ownership and company size have no effect on Firm Performance while simultaneously Envirometal Disclosure, Insider Ownership and Firm Size with Leverage as a Control Variable on Firm Performance.